Electrophotographic photosensitive member, process cartridge, and electrophotographic apparatus

By introducing specific distributions of inorganic particles and resin particles into the surface layer of the electrophotographic photosensitive member, the problems of insufficient wear resistance and deep cracks in the prior art are solved, and higher wear resistance and more stable Image quality.

CN111474834BActive Publication Date: 2024-12-27CANON KK
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202010075229.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-01-24
Filing Date
2020-01-22
Publication Date
2024-12-27
Estimated Expiration
2040-01-22

AI Technical Summary

Technical Problem

The existing electrophotographic photosensitive members are not able to resist wear in long-term use, and deep cracks are prone to occur, and the wear and deep cracks of the surface layer are difficult to effectively reduce.

Method used

Inorganic particles having 5 nm or more and 50 nm or less and resin particles having 0.1 μm or more and 5.0 μm or less are introduced into the surface layer of the electrophotographic photosensitive member, and a specific distribution relationship between inorganic particles and resin particles is satisfied in any cross-section of the surface layer. To improve elastic utilization and inhibit the brittleness of inorganic particles.

Benefits of technology

By optimizing the distribution of inorganic particles and resin particles, the wear of the surface layer and the occurrence of deep cracks are significantly reduced, and the wear resistance of the electrophotographic photosensitive member is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN111474834B_ABST
    Figure CN111474834B_ABST
Patent Text Reader

Abstract

The present invention relates to an electrophotographic photosensitive member, a process box and an electrophotographic apparatus. The electrophotographic photosensitive member includes: a support; a charge generating layer; and a charge transporting layer, the charge generating layer and the charge transporting layer being arranged on the support, wherein the surface layer of the electrophotographic photosensitive member contains: inorganic particles having an average particle size (Lα) of primary particles of 5 nm or more and 50 nm or less; and resin particles having an average particle size (Lβ) of primary particles of 0.1 μm or more and 5.0 μm or less, and wherein in any cross section of the surface layer, "(Smα) / (Sα)≥0.3" is satisfied, wherein a region within (Lβ / 2) from the surface of each resin particle is defined as a region (M), the sum of the cross-sectional areas of the inorganic particles in any cross section is represented by (Sα), and the sum of the cross-sectional areas of the inorganic particles contained in the region (M) is represented by (Smα).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to an electrophotographic photosensitive member, and a process cartridge and an electrophotographic apparatus each including the electrophotographic photosensitive member. Background Art

[0002] In recent years, as a result of the diversification of users of electrophotographic apparatuses, it has been required that output images have higher image quality than in the prior art and have no change in image quality during long-term use.

[0003] In Japanese Patent Application Laid-Open No. 2017-58524, as a technology for improving wear resistance, there is disclosed a technology regarding an electrophotographic photosensitive member including a surface layer containing: a charge transporting substance; surface-treated inorganic particles each having a high volume resistivity; and organic fine particles.

[0004] In addition, in Japanese Patent Application Laid-Open No. 2017-125946, as a technology for improving durability while maintaining satisfactory cleanability, the following technology is disclosed. Metal oxide fine particles to be dispersed in the protective layer are treated with two surface treatment agents, and a part of the metal oxide fine particles with the two surface treatment agents is maintained on the surface of the fluororesin fine particles, thereby suppressing the aggregation of the fluororesin fine particles in the protective layer to improve their dispersibility. In addition to this, the fluororesin fine particles are fixed to the binder resin via the metal oxide fine particles, whereby the fluororesin fine particles are not easily detached from the protective layer.

[0005] As described above, in order to reduce changes in image quality during use, it is important to reduce the amount of wear of the electrophotographic photosensitive member.

[0006] According to studies conducted by the present inventors, it was found that in each of the electrophotographic photosensitive members described in Japanese Patent Application Laid-Open No. 2017-58524 and Japanese Patent Application Laid-Open No. 2017-125946, the introduction of inorganic fine particles produces a brittle film, and therefore, the wear resistance is insufficient or deep flaws are generated by long-term use in some cases.

[0007] Therefore, an object of the present disclosure is to provide an electrophotographic photosensitive member having higher wear resistance and being less prone to having deep cracks. Summary of the invention

[0008] The above-mentioned object is achieved by the following disclosure. That is, according to one aspect of the present disclosure, there is provided an electrophotographic photosensitive member, comprising: a support; a charge generating layer; and a charge transporting layer, the charge generating layer and the charge transporting layer being arranged on the support, wherein the surface layer of the electrophotographic photosensitive member comprises: inorganic particles (α) having an average particle size (Lα) of primary particles of 5 nm or more and 50 nm or less; and resin particles (β) having an average particle size (Lβ) of primary particles of 0.1 μm or more and 5.0 μm or less, and wherein in any cross section of the surface layer, the following formula (1) is satisfied, wherein a region within a distance (Lβ / 2) from the surface of each resin particle (β) is defined as a region (M), the sum of the cross-sectional areas of the inorganic particles (α) present in the cross section is represented by (Sα), and the sum of the cross-sectional areas of the inorganic particles (α) contained in the region (M) is represented by (Smα).

[0009] (Smα) / (Sα)≥0.3 Formula (1)

[0010] Further features of the present invention will become apparent from the following description of exemplary embodiments with reference to the attached drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0011] Figure 1 : is a diagram showing an example of a schematic configuration of an electrophotographic image forming apparatus including a process cartridge including an electrophotographic photosensitive member according to one aspect of the present disclosure.

[0012] Figure 2A It is a graph showing the relationship between the region (M) and the average particle size (Lβ) of primary particles of the resin particles (β).

[0013] Figure 2B It is a graph showing the relationship between the region (M′) and the average particle size (Lβ) of primary particles of the resin particles (β). DETAILED DESCRIPTION

[0014] Hereinafter, the present disclosure will be described in detail through preferred embodiments.

[0015] According to one aspect of the present disclosure, an electronic photographic photosensitive member includes: a support; a charge generating layer; and a charge transporting layer, wherein the charge generating layer and the charge transporting layer are arranged on the support, wherein the surface layer of the electronic photographic photosensitive member contains: inorganic particles (α) having an average particle size (Lα) of primary particles of 5 nm or more and 50 nm or less; and resin particles (β) having an average particle size (Lβ) of primary particles of 0.1 μm or more and 5.0 μm or less, and wherein in any cross-section of the surface layer, the following formula (1) is satisfied, wherein a region within a distance (Lβ / 2) from the surface of each resin particle (β) is defined as a region (M), the sum of the cross-sectional areas of the inorganic particles (α) present in the cross-section is represented by (Sα), and the sum of the cross-sectional areas of the inorganic particles (α) contained in the region (M) is represented by (Smα).

[0016] (Smα) / (Sα)≥0.3 Formula (1)

[0017] According to the research conducted by the present inventors, it was found that in the configuration of Japanese Patent Application Laid-Open No. 2017-58524 or Japanese Patent Application Laid-Open No. 2017-125946, the surface layer contains inorganic particles, and therefore, although its hardness is improved, it becomes brittle as a film. Therefore, depending on the use environment, wear resistance is not significantly exhibited or deep cracks may occur.

[0018] In addition, it was found that in the configuration of Japanese Patent Application Laid-Open No. 2017-125946, a rise in residual potential was observed in some cases.

[0019] In order to solve the problems arising in the above-mentioned prior art, the inventors have studied the configuration of the resin fine particles and inorganic particles in the film. As a result, it was found that the wear of the surface layer and the occurrence of deep cracks in the surface layer that have occurred in the prior art can be reduced under the following conditions: the surface layer contains inorganic particles (α) having an average particle size (Lα) of primary particles of 5nm or more and 50nm or less and resin particles (β) having an average particle size (Lβ) of primary particles of 0.1μm or more and 5.0μm or less; and in any cross section of the surface layer, formula (1) is satisfied, wherein the area within (Lβ / 2) from the surface of each resin particle (β) is defined as region (M), the sum of the cross-sectional areas of the inorganic particles (α) present in the arbitrary cross section is represented by (Sα), and the sum of the cross-sectional areas of the inorganic particles (α) contained in the region (M) is represented by (Smα).

[0020] (Smα) / (Sα)≥0.3 Formula (1)

[0021] It is presumed that the mechanism by which the wear of the surface layer and the occurrence of deep cracks in the surface layer, which are problems of the prior art, are reduced by the configuration of one aspect of the present disclosure is as follows.

[0022] The surface layer containing inorganic particles is reduced in elasticity so that it becomes brittle as a film, so in some cases the wear resistance is insufficient or deep cracks are generated in some cases. In order to eliminate these problems, even when the resin particles are introduced into the surface layer of the electrophotographic photosensitive member together with the inorganic particles, the elasticity is partially insufficient depending on their presence in the surface layer, and as a result, the occurrence of deep cracks cannot be eliminated. According to the configuration of one aspect of the present disclosure, the inorganic particles are arranged near the resin particles, so the elasticity of the resin particles can be fully utilized. Therefore, the reduction in elasticity due to the introduction of the inorganic particles can be suppressed to reduce the brittleness of the film.

[0023] As described above, the effects of the present disclosure can be achieved through the interaction of the components with each other.

[0024] <Inorganic Particles (α)>

[0025] Examples of the inorganic particles (α) include silicon oxide (silicon dioxide), magnesium oxide, zinc oxide, lead oxide, aluminum oxide (alumina), zirconium oxide, tin oxide, titanium oxide (titania), niobium oxide, molybdenum oxide, and vanadium oxide. Among them, silicon oxide (silicon dioxide, SiO 2 ) and aluminum oxide (aluminum oxide, Al 2 O 3 ).

[0026] As the inorganic particles contained in the surface layer of the electrophotographic photosensitive member according to one aspect of the present disclosure, from the viewpoint of suppressing the occurrence of black spots and white spots in an image printed using the electrophotographic photosensitive member or cracks in the electrophotographic photosensitive member, inorganic particles having an average particle diameter (Lα) of primary particles of 5 nm or more and 50 nm or less are used.

[0027] From the viewpoint of affinity with the resin particles, the inorganic particles each preferably have a surface treated with silicone oil or at least one compound selected from the group consisting of compounds represented by structural formula (1) and structural formula (2):

[0028]

[0029] In the structural formulas (1) and (2), R 1 ~R 3 Each independently represents an alkoxy group or an alkyl group, provided that R 1 ~R 3 At least two of them each represent an alkoxy group; R 4 represents vinyl, 1-methylvinyl, acryloyloxy or methacryloyloxy; R 5represents an acryloyloxy group or a methacryloyloxy group; and "n" represents an integer of 1 or more and 6 or less.

[0030] Specific examples of the compounds represented by the structural formula (1) and the structural formula (2) include compounds represented by the following structural formulas (P-1) to (P-21).

[0031] H 2 C=CHSi(CH 3 )(OCH 3 ) 2 (P-1)

[0032] H 2 C=CHSi(OCH 3 ) 3 (P-2)

[0033] H 2 C=CHCOO(CH 2 ) 2 Si(CH 3 )(OCH 3 ) 2 (P-3)

[0034] H 2 C=CHCOO(CH 2 ) 2 Si(OCH 3 ) 3 (P-4)

[0035] H 2 C=CHCOO(CH 2 ) 3 Si(CH 3 )(OCH 3 ) 2 (P-5)

[0036] H 2 C=CHCOO(CH 2 ) 3 Si(OCH 3 ) 3 (P-6)

[0037] H 2 C=C(CH 3 )COO(CH 2 ) 2 Si(CH 3 )(OCH 3 ) 2 (P-7)

[0038] H 2 C=C(CH s)COO(CH 2 ) 2 Si(AND 3 ) 3 (P-8)

[0039] H2C=C(CH3)COO(CH 2 ) 3 Si(CH 3 )(AND 3 ) 2 (P-9)

[0040] H 2 C=C(CH 3 )COO(CH 2 ) 3 Si(AND 3 ) 3 (P-10)

[0041] H 2 C=CHSi(C 2 H 5 )(AND 3 ) 2 (P-11)

[0042] H 2 C=C(CH 3 )Si(AND 3 ) 3 (P-12)

[0043] H 2 C=C(CH 3 )Si(OC 2 H 6 ) 3 (P-13)

[0044] H 2 C=CHSi(OCH 3 ) 3 (P-14)

[0045] H 2 C=C(CH 3 )Si(CH 3 )(AND 3 ) 2 (P-15)

[0046] H 2 C=CHCOOSi(OCH 3 ) 3 (P-16)

[0047] H 2 C=CHCOOSi(OC2 H 5 ) 3 (P-17)

[0048] H 2 C=CHCOOSi(OC 2 H 5 ) 3 (P-18)

[0049] H 2 C=C(CH 3 )COOSi(OCH 3 ) 3 (P-19)

[0050] H 2 C=C(CH 3 )COOSi(OC 2 H 5 ) 3 (P-20)

[0051] H 2 C=C(CH 3 )COO(CH 2 ) 3 Si(OC 2 H 5 ) 3 (P-21)

[0052] <Resin Particles (β)>

[0053] As the resin particles contained in the surface layer of the electrophotographic photosensitive member according to one aspect of the disclosure, particles of polymethyl methacrylate resin (PMMA), melamine resin of melamine-formaldehyde polycondensation type or melamine-benzoguanamine-formaldehyde co-condensation type, benzoguanamine resin, styrene acrylic resin, silicone resin or fluororesin can be used. Among them, particles of a resin selected from PMMA, melamine resin of melamine-formaldehyde polycondensation type and fluororesin are preferably used.

[0054] The average particle size (Lβ) of the primary particles of the resin particles is determined from the cross section of the surface layer of the electrophotographic photosensitive member. Specifically, 50 resin particles in the cross section of the surface layer are observed to obtain an image. The image is subjected to ellipse fitting to obtain the longest diameter. The average value of the 10 largest longest diameters among the 50 longest diameters obtained is defined as the average particle size (Lβ) of the primary particles of the resin particles. The average particle size (Lβ) is 0.1 μm or more and 5.0 μm or less, and from the viewpoint of suppressing black spots and white spots, it is more preferably 0.1 μm or more and 1.5 μm or less.

[0055] <Area(M)>

[0056] As Figure 2A shown, region (M) is a region within a distance (Lβ / 2) from the outermost surface of each resin particle.

[0057] When the sum of the cross-sectional areas (Sα) of the inorganic particles (α) present in any cross-section of the surface layer and the sum of the cross-sectional areas (Smα) of the inorganic particles (α) contained in region (M) in the cross-section satisfy formula (1), that is, when the inorganic particles are present near the resin particles, the elasticity of the resin particles can be effectively utilized. Therefore, the effects of the present disclosure can be obtained. In addition, when the following formula (2) is satisfied, that is, when many inorganic particles are present near the resin particles, the surface layer is more likely to obtain the elasticity of the resin particles. Therefore, further effects can be obtained from the viewpoint of the abrasion resistance of the film.

[0058] (Smα) / (Sα)≥0.5 Formula (2)

[0059] <Region (M′)>

[0060] As Figure 2B shown, region (M′) is a region within a distance (Lβ / 3) from the outermost surface of each resin particle in any cross-section of the surface layer.

[0061] When the relationship between the total area (Sα) of the inorganic particles present in any cross-section of the surface layer and the area (Sm′α) of the inorganic particles present in region (M′) satisfies the following formula (3), the surface layer can more effectively utilize the elasticity of the resin particles. That is, when many inorganic particles are present closer to the resin particles, further effects can be obtained from the viewpoint of the abrasion resistance of the film.

[0062] (Sm′α) / (Sα)≥0.3 Formula (3)

[0063] <Measurement methods for Sα, Smα, and Sm′α>

[0064] The measurement method of Sα is carried out as follows, for example.

[0065] The photosensitive member is cut at an arbitrary position to cut out a piece with a size of 10 mm square, and the obtained cross-section is processed into a smooth cross-section. Magnified observation is performed from the cross-section direction, and the observed image is captured. Sα is calculated based on the sum of the areas occupied by the inorganic fine particles contained in the cross-section from the captured image. In the same manner as the calculation direction of Sα, Smα and Sm′α are obtained within the ranges of region (M) and region (M′).

[0066] For accurate calculation of Sα, Smα, and Sm′α, the cross-section is preferably prepared by an ion beam or the like, and the cross-section is preferably observed by a scanning electron microscope or the like.

[0067] In addition, in the calculation of Sα, Smα, and Sm′α, image processing such as binarization may be used after the inorganic fine particles are identified by elemental analysis.

[0068] The production method of the photosensitive member according to one aspect of the present disclosure is not limited as long as the characteristics of the present disclosure are satisfied. However, as a method of more efficiently obtaining a photosensitive member, composite particles of inorganic particles and resin particles are preferably used.

[0069] [Electrophotographic photosensitive member]

[0070] An electrophotographic photosensitive member according to one aspect of the present disclosure includes a charge generating layer, a charge transporting layer, and a surface layer in this order on a support.

[0071] The production method of an electrophotographic photosensitive member according to one aspect of the present disclosure is, for example, a method involving: preparing a coating liquid for each layer described later; applying each coating liquid in a desired layer order; and drying each coating liquid. In this case, examples of the coating liquid application method include dip coating, spray coating, inkjet coating, roller coating, die coating, blade coating, curtain coating, wire rod coating, and ring coating. Among them, dip coating is preferred from the viewpoint of efficiency and productivity.

[0072] Now, the various layers are described.

[0073] <Support>

[0074] In one aspect of the present disclosure, the electrophotographic photosensitive member includes a support. In one aspect of the present disclosure, the support is preferably a conductive support having conductivity. In addition, examples of the shape of the support include cylindrical, belt-shaped, and sheet-shaped. Among them, a cylindrical support is preferred. In addition, the surface of the support may be subjected to, for example, electrochemical treatment such as anodizing, sandblasting, or cutting treatment.

[0075] As a material for the support, metal, resin, glass or the like is preferable.

[0076] Examples of the metal include aluminum, iron, nickel, copper, gold, stainless steel, and alloys thereof. Among them, an aluminum support using aluminum is preferred.

[0077] In addition, conductivity may be imparted to the resin or glass through a process involving, for example, mixing the resin or glass with a conductive material or coating the resin or glass with a conductive material.

[0078] <Conductive layer>

[0079] In one aspect of the present disclosure, a conductive layer may be disposed on the support body, and the conductive layer may conceal cracks and irregularities in the surface layer of the support body and control reflection of light on the surface of the support body.

[0080] The conductive layer preferably contains conductive particles and a resin.

[0081] The material for the conductive particles is, for example, a metal oxide, a metal or carbon black. Examples of metal oxides include zinc oxide, aluminum oxide, indium oxide, silicon oxide, zirconium oxide, tin oxide, titanium oxide, magnesium oxide, antimony oxide and bismuth oxide. Examples of metals include aluminum, nickel, iron, nickel-chromium alloy, copper, zinc and silver.

[0082] Among them, metal oxides are preferably used as the conductive particles, and in particular, titanium oxide, tin oxide, and zinc oxide are more preferably used.

[0083] When a metal oxide is used as the conductive particles, the surface of the metal oxide may be treated with a silane coupling agent or the like, or the metal oxide may be doped with an element such as phosphorus or aluminum, or an oxide thereof.

[0084] In addition, each of the conductive particles may have a laminated structure having a core particle and a coating layer coating the particle. Examples of the core particle include titanium oxide, barium sulfate, and zinc oxide. The coating layer is, for example, a metal oxide such as tin oxide.

[0085] In addition, when metal oxides are used as the conductive particles, their volume average particle diameter is preferably 1 nm or more and 500 nm or less, more preferably 3 nm or more and 400 nm or less.

[0086] Examples of the resin include polyester resins, polycarbonate resins, polyvinyl acetal resins, acrylic resins, silicone resins, epoxy resins, melamine resins, polyurethane resins, phenolic resins, and alkyd resins.

[0087] In addition, the conductive layer may further contain a masking agent such as silicone oil, resin particles or titanium oxide.

[0088] The average thickness of the conductive layer is preferably 1 μm or more and 50 μm or less, particularly preferably 3 μm or more and 40 μm or less.

[0089] The conductive layer can be formed by preparing a conductive layer coating liquid containing the above-mentioned materials and a solvent, forming a coating film of the coating liquid, and drying the coating film. Examples of solvents for the coating liquid include alcohol solvents, sulfoxide solvents, ketone solvents, ether solvents, ester solvents, and aromatic hydrocarbon solvents. As a dispersion method for dispersing conductive particles in a conductive layer coating liquid, a method using a paint stirrer, a sand mill, a ball mill, and a liquid collision type high-speed disperser is given.

[0090] <Base Coating>

[0091] In one aspect of the present disclosure, a primer layer may be disposed on the support or the conductive layer. The configuration of the primer layer may improve the adhesion function between the layers and impart a charge injection suppression function.

[0092] The primer layer preferably contains a resin. Alternatively, the primer layer can be formed as a cured film by polymerizing a composition containing a monomer having a polymerizable functional group.

[0093] Examples of the resin include polyester resins, polycarbonate resins, polyvinyl acetal resins, acrylic resins, epoxy resins, melamine resins, polyurethane resins, phenolic resins, polyvinylphenolic resins, alkyd resins, polyvinyl alcohol resins, polyethylene oxide resins, polypropylene oxide resins, polyamide resins, polyamic acid resins, polyimide resins, polyamideimide resins, and cellulose resins.

[0094] Examples of the polymerizable functional group of the monomer having a polymerizable functional group include an isocyanate group, a blocked isocyanate group, a methylol group, an alkylated methylol group, an epoxy group, a metal alkoxide group, a hydroxyl group, an amino group, a carboxyl group, a thiol group, a carboxylic anhydride group, and a carbon-carbon double bond group.

[0095] In order to improve the electrical characteristics, the undercoat layer may further contain an electron transporting substance, a metal oxide, a metal, a conductive polymer, etc. Among them, the electron transporting substance and the metal oxide are preferably used.

[0096] Examples of electron transporting substances include quinone compounds, imide compounds, benzimidazole compounds, cyclopentadienyl compounds, fluorenone compounds, xanthone compounds, benzophenone compounds, cyanovinyl compounds, halogenated aryl compounds, silole compounds and boron-containing compounds. An electron transporting substance having a polymerizable functional group can be used as the electron transporting substance and copolymerized with the above-mentioned monomer having a polymerizable functional group to form a primer layer as a cured film.

[0097] Examples of metal oxide particles include indium tin oxide, tin oxide, indium oxide, titanium oxide, zinc oxide, aluminum oxide, and silicon dioxide. Examples of metals include gold, silver, and aluminum.

[0098] In addition, the undercoat layer may further contain additives.

[0099] The average thickness of the primer layer is preferably 0.1 μm or more and 50 μm or less, more preferably 0.2 μm or more and 40 μm or less, particularly preferably 0.3 μm or more and 30 μm or less.

[0100] The undercoat layer can be formed by preparing an undercoat layer coating solution comprising the above-mentioned materials and a solvent, forming a coating film of the coating solution, and drying and / or curing the coating film. Examples of solvents for the coating solution include alcohol solvents, ketone solvents, ether solvents, ester solvents, and aromatic hydrocarbon solvents.

[0101] <Photosensitive layer>

[0102] The photosensitive layer of the electrophotographic photosensitive member is mainly classified into (1) a laminated photosensitive layer and (2) a single-layer photosensitive layer. (1) The laminated photosensitive layer has a charge generating layer containing a charge generating substance and a charge transporting layer containing a charge transporting substance. (2) The single-layer photosensitive layer has a photosensitive layer containing both a charge generating substance and a charge transporting substance.

[0103] When the electrophotographic photosensitive member does not include a protective layer described later, in (1) a laminated photosensitive layer, the charge transport layer is a surface layer of one aspect of the present disclosure, and in (2) a single layer photosensitive layer, the photosensitive layer is a surface layer of one aspect of the present disclosure.

[0104] (1) Laminated photosensitive layer

[0105] The laminated photosensitive layer is a laminated photosensitive layer including a charge generating layer and a charge transporting layer.

[0106] (1) Charge Generation Layer

[0107] The charge generating layer preferably contains a charge generating substance and a resin.

[0108] Examples of the charge generating material include azo pigments, perylene pigments, polycyclic quinone pigments, indigo pigments, and phthalocyanine pigments. Among them, azo pigments and phthalocyanine pigments are preferred. Among phthalocyanine pigments, oxytitanium phthalocyanine pigments, chlorogallium phthalocyanine pigments, and hydroxygallium phthalocyanine pigments are preferred.

[0109] The content of the charge generating material in the charge generating layer is preferably 40% by mass or more and 85% by mass or less, and more preferably 60% by mass or more and 80% by mass or less, based on the total mass of the charge generating layer.

[0110] Examples of the resin include polyester resins, polycarbonate resins, polyvinyl acetal resins, polyvinyl butyral resins, acrylic resins, silicone resins, epoxy resins, melamine resins, polyurethane resins, phenolic resins, polyvinyl alcohol resins, cellulose resins, polystyrene resins, polyvinyl acetate resins, and polyvinyl chloride resins. Among them, polyvinyl butyral resins are more preferred.

[0111] In addition, the charge generation layer may further contain additives such as an antioxidant or a UV absorber, etc. Specific examples thereof include hindered phenol compounds, hindered amine compounds, sulfur compounds, phosphorus compounds and benzophenone compounds.

[0112] The average thickness of the charge generating layer is preferably 0.1 μm or more and 1 μm or less, and more preferably 0.15 μm or more and 0.4 μm or less.

[0113] The charge generation layer can be formed by preparing a charge generation layer coating liquid containing the above-mentioned materials and a solvent, forming a coating film of the coating liquid, and drying the coating film. Examples of the solvent used for the coating liquid include alcohol solvents, sulfoxide solvents, ketone solvents, ether solvents, ester solvents, and aromatic hydrocarbon solvents.

[0114] (2) Charge transport layer

[0115] The charge transporting layer preferably contains a charge transporting substance and a resin.

[0116] Examples of the charge transporting substance include polycyclic aromatic compounds, heterocyclic compounds, hydrazone compounds, styryl compounds, enamine compounds, benzidine compounds, triarylamine compounds, and resins having groups derived from each of these substances. Among them, triarylamine compounds and benzidine compounds are preferred.

[0117] The content of the charge transporting substance in the charge transporting layer is preferably 25% by mass or more and 70% by mass or less, and more preferably 30% by mass or more and 55% by mass or less, based on the total mass of the charge transporting layer.

[0118] Examples of the resin include polyester resins, polycarbonate resins, acrylic resins, and polystyrene resins. Among them, polycarbonate resins and polyester resins are preferred. As the polyester resin, polyarylate resins are particularly preferred.

[0119] The content ratio (mass ratio) between the charge transporting substance and the resin is preferably from 4:10 to 20:10, more preferably from 5:10 to 12:10.

[0120] In addition, the charge transport layer may contain additives such as antioxidants, UV absorbers, plasticizers, leveling agents, lubricity imparting agents or wear resistance improving agents. Specific examples thereof include hindered phenol compounds, hindered amine compounds, sulfur compounds, phosphorus compounds, benzophenone compounds, siloxane modified resins, silicone oils, fluororesin particles, polystyrene resin particles, polyethylene resin particles, silica particles, alumina particles and boron nitride particles.

[0121] The average thickness of the charge transport layer is 5 μm or more and 50 μm or less, more preferably 8 μm or more and 40 μm or less, particularly preferably 10 μm or more and 30 μm or less.

[0122] The charge transport layer can be formed by preparing a charge transport layer coating liquid comprising the above-mentioned materials and a solvent, forming a coating film of the coating liquid, and drying the coating film. When the charge transport layer is a surface layer in one aspect of the present disclosure, the charge transport layer coating liquid further comprises inorganic particles (α) and resin particles (β). Examples of solvents for the coating liquid include alcohol solvents, ketone solvents, ether solvents, ester solvents, and aromatic hydrocarbon solvents. Among these solvents, ether solvents or aromatic hydrocarbon solvents are preferred.

[0123] (2) Single-layer photosensitive layer

[0124] The single-layer photosensitive layer can be formed by preparing a photosensitive layer coating liquid containing a charge generating substance, a charge transporting substance, a binder resin and a solvent, forming a coating film of the coating liquid and drying the coating film. Examples of the charge generating substance, the charge transporting substance and the binder resin are the same as the examples of the materials in the section "(1) Laminated photosensitive layer".

[0125] When the single-layer type photosensitive layer is a surface layer in one aspect of the present disclosure, the single-layer type photosensitive layer contains inorganic particles (α) and resin particles (β).

[0126] <Protective layer>

[0127] In the electrophotographic photosensitive member according to one aspect of the present disclosure, a protective layer may be arranged on the photosensitive layer as a surface layer. The arrangement of the protective layer can improve durability.

[0128] The surface layer preferably contains inorganic particles and resin particles, a charge transporting substance and a resin.

[0129] Examples of the charge transporting substance include polycyclic aromatic compounds, heterocyclic compounds, hydrazone compounds, styryl compounds, enamine compounds, benzidine compounds, triarylamine compounds, and resins having groups derived from each of these substances. Among them, triarylamine compounds and benzidine compounds are preferred.

[0130] Examples of the resin include polyester resins, acrylic resins, phenoxy resins, polycarbonate resins, polystyrene resins, phenolic resins, melamine resins, and epoxy resins. Among them, polycarbonate resins, polyester resins, and acrylic resins are preferred.

[0131] In addition, the protective layer can be formed into a cured film by polymerizing a composition containing a monomer having a polymerizable functional group. As the reaction in this case, for example, thermal polymerization, photopolymerization, and radiation polymerization are given. Examples of the polymerizable functional group of the monomer having a polymerizable functional group include acryloyl and methacryloyl. A material having a charge transporting ability can be used as the monomer having a polymerizable functional group.

[0132] The protective layer may further contain additives such as antioxidants, UV absorbers, plasticizers, leveling agents or lubricity imparting agents in addition to the inorganic particles and resin particles according to one aspect of the present disclosure. Specific examples thereof include hindered phenol compounds, hindered amine compounds, sulfur compounds, phosphorus compounds, benzophenone compounds, siloxane-modified resins and silicone oils.

[0133] The average thickness of the protective layer is preferably 0.5 μm or more and 10 μm or less, and more preferably 1 μm or more and 7 μm or less.

[0134] The protective layer can be formed by preparing a protective layer coating liquid containing the above-mentioned materials and a solvent, forming a coating film of the coating liquid, and drying the coating film. Examples of the solvent used for the coating liquid include alcohol solvents, ketone solvents, ether solvents, sulfoxide solvents, ester solvents, and aromatic hydrocarbon solvents.

[0135] [Process cartridge and electrophotographic apparatus]

[0136] A process cartridge according to one aspect of the present disclosure integrally supports the aforementioned electrophotographic photosensitive member, and at least one unit selected from the group consisting of a charging unit, a developing unit, a transfer unit, and a cleaning unit, and is detachably mountable to a main body of an electrophotographic apparatus.

[0137] In addition, an electrophotographic apparatus according to one aspect of the present disclosure includes the aforementioned electrophotographic photosensitive member, and at least one unit selected from the group consisting of a charging unit, an exposure unit, a developing unit, and a transfer unit.

[0138] An example of a schematic configuration of an electrophotographic apparatus including a process cartridge containing an electrophotographic photosensitive member is shown in Figure 1 Shown in.

[0139] A cylindrical electrophotographic photosensitive member 1 is rotationally driven around an axis 2 in a direction indicated by an arrow at a predetermined peripheral speed. The surface of the electrophotographic photosensitive member 1 is charged to a predetermined positive or negative potential by a charging unit 3. Figure 1In the figure, a roller charging system based on a roller-type charging member is shown, but a charging system such as a corona charging system, a proximity charging system, or an injection charging system may be adopted. The charged surface of the electrophotographic photosensitive member 1 is irradiated with exposure light 4 from an exposure unit (not shown). As a result, an electrostatic latent image corresponding to the target image information is formed thereon. The electrostatic latent image formed on the surface of the electrophotographic photosensitive member 1 is developed with a toner stored in a developing unit 5, and a toner image is formed on the surface of the electrophotographic photosensitive member 1. The toner image formed on the surface of the electrophotographic photosensitive member 1 is transferred to a transfer material 7 by a transfer unit 6. The transfer material 7 to which the toner image is transferred is conveyed to a fixing unit 8, a process for fixing the toner image is performed, and it is printed out to the outside of the electrophotographic apparatus. The electrophotographic apparatus may include a cleaning unit 9 for removing deposits such as toner remaining on the surface of the electrophotographic photosensitive member 1 after transfer. In addition, a so-called cleaner-less system configured to remove deposits with a developing unit or the like without separately configuring a cleaning unit may be used. The electrophotographic apparatus may include a destaticizing mechanism configured to subject the surface of the electrophotographic photosensitive member 1 to destaticizing treatment with pre-exposure light 10 from a pre-exposure unit (not shown). In addition, a guide unit 12 such as a guide rail may be configured to detachably mount the process cartridge according to one aspect of the present disclosure to the main body of the electrophotographic apparatus.

[0140] The electrophotographic photosensitive member according to one aspect of the present disclosure can be used for, for example, a laser beam printer, an LED printer, a copier, a facsimile machine, and multifunction peripherals thereof.

[0141] Example

[0142] The present disclosure will be described in more detail below by examples and comparative examples. The present disclosure is by no means limited to the following examples, and various modifications may be made without departing from the gist of the present disclosure. In the description of the following examples, "parts" are based on mass, unless otherwise indicated.

[0143] (Production Example of Pellets S1)

[0144] 100 parts by mass of untreated silica having an average particle size of 40 nm was placed in a 2L autoclave with a stirrer and heated to 200°C while fluidizing by stirring. While maintaining the fluidized state, the interior of the autoclave was purged with nitrogen and the reaction vessel was hermetically sealed. While stirring the silica, dimethyl silicone oil (viscosity = 50 mm 2 / s) as a surface treatment agent was sprayed in a manner that the amount after treatment was adjusted to 20 parts by mass, and stirring was continued for 30 minutes. Thereafter, the temperature of the resultant was raised to 300°C under stirring, and further stirred for 2 hours. Silica was taken out from the autoclave. Thus, S1 was obtained.

[0145] (Production Example of Pellets S2)

[0146] The particles were produced in the same manner as in the production example of the particles S1, except that the amounts of silica and silicone oil were changed as shown in Table 1. The obtained particles were named "S2". The details are shown in Table 1.

[0147] (Production Example of Pellets S3)

[0148] 100 parts of silica (average primary particle diameter: 40 nm) and 500 parts of toluene were mixed under stirring, and 0.8 parts of octyltriethoxysilane (product name: KBE3083, manufactured by Shin-Etsu Chemical Co., Ltd.) as a surface treatment agent was added, followed by stirring for 6 hours.

[0149] Thereafter, toluene was removed by distillation under reduced pressure, and the residue was dried by heating at 140° C. for 6 hours, thereby obtaining surface-treated silica S3.

[0150] (Production Example of Granules S4 and S5)

[0151] Particles were produced in the same manner as in the production example of particle S3, except that the amounts of silica and the surface treatment agent were changed as shown in Table 1. The obtained particles were named "particles S4 and particles S5". The details are shown in Table 1.

[0152] (Production Example of Pellets A1)

[0153] 100 parts of alumina particles (average primary particle size: 10 nm, specific surface area: 150 m 2 / g) and 500 parts of toluene were mixed under stirring. And 1.03 parts of silicone oil (product name: KBE3083, manufactured by Shin-Etsu Chemical Co., Ltd.) as a surface treatment agent was added, followed by stirring for 6 hours.

[0154] Thereafter, toluene was removed by distillation under reduced pressure, and the residue was dried by heating at 140° C. for 6 hours, thereby obtaining surface-treated aluminum oxide particles A1.

[0155] (Production Example of Pellets A2)

[0156] 100 parts of alumina particles (average primary particle size: 18 nm, specific surface area: 65 m 2 / g) and 500 parts of toluene were mixed under stirring, and 1.03 parts of octyltriethoxysilane (product name: KBE3083, manufactured by Shin-Etsu Chemical Co., Ltd.) as a surface treatment agent was added, followed by stirring for 6 hours. Thereafter, toluene was removed by distillation under reduced pressure, and the residue was dried by heating at 140° C. for 6 hours, thereby obtaining surface-treated aluminum oxide particles A2.

[0157] (Production Example of Pellets A3)

[0158] 100 parts of alumina particles (average primary particle size: 18 nm, specific surface area: 65 m 2 / g) and 500 parts of toluene were mixed under stirring, and 1.1 parts of octyltriethoxysilane (product name: KBE3083, manufactured by Shin-Etsu Chemical Co., Ltd.) as a surface treatment agent was added, followed by stirring for 6 hours.

[0159] Thereafter, toluene was removed by distillation under reduced pressure, and the residue was dried by heating at 140° C. for 6 hours, thereby obtaining surface-treated aluminum oxide particles A3.

[0160] (Production Example of Pellets A4)

[0161] 100 parts of alumina particles (average primary particle size: 18 nm, specific surface area: 65 m 2 / g) and 500 parts of toluene were mixed under stirring, and 1.03 parts of Compound P-10 (product name: KBE3083, manufactured by Shin-Etsu Chemical Co., Ltd.) as a surface treatment agent was added, followed by stirring for 6 hours.

[0162] Thereafter, toluene was removed by distillation under reduced pressure, and the residue was dried by heating at 140° C. for 6 hours, thereby obtaining surface-treated aluminum oxide particles A4.

[0163] Table 1

[0164]

[0165] (Production Example of Composite Particles H1)

[0166] 200 parts of particles S1 and 100 parts of melamine-formaldehyde condensate particles having an average particle size of 0.4 μm (product name: EPOSTAR S6, manufactured by Nippon Shokubai Co., Ltd.) were mixed and stirred in a coffee grinder for 10 seconds, which was repeated 10 times to obtain composite particles H1.

[0167] (Production Example of Composite Particles H2 to H24)

[0168] Composite particles were obtained in the same manner as in the production example of composite particle H1 except that the inorganic particles and resin particles shown in Table 2 were respectively used and the conditions were changed as shown in Table 2. The obtained composite particles were referred to as "composite particles H2 to H24".

[0169] The resin particles (β) used for the production of the composite particles H2 to H24 are as follows.

[0170] Melamine-formaldehyde condensate (S6) (Product name: EPOSTAR (trademark) S6, manufactured by Nippon Shokubai Co., Ltd.)

[0171] Melamine-formaldehyde condensate (S12) (Product name: EPOSTAR (trademark) S12, manufactured by Nippon Shokubai Co., Ltd.)

[0172] Melamine-formaldehyde condensate (SS) (Product name: EPOSTAR (trademark) SS, manufactured by Nippon Shokubai Co., Ltd.)

[0173] PMMA (MA1002) (Product name: EPOSTAR (trademark) MA1002, manufactured by Nippon Shokubai Co., Ltd.)

[0174] PMMA (MA1004) (Product name: EPOSTAR (trademark) MA1004, manufactured by Nippon Shokubai Co., Ltd.)

[0175] Table 2

[0176]

[0177] (Production Example of Protective Layer Coating Liquid 1)

[0178] 70 parts of a hole transporting compound represented by the following structural formula (3), 5 parts of particles H1, 30 parts of 1,1,2,2,3,3,4-heptafluorocyclopentane and 30 parts of 1-propanol were mixed to obtain a protective layer coating liquid 1.

[0179]

[0180] (Production Example of Protective Layer Coating Liquid 2 to Protective Layer Coating Liquid 24)

[0181] Protective layer coating liquids 2 to 24 were obtained in the same manner as in Production Example of the protective layer coating liquid 1, except that the particles shown in Table 3 were used and the conditions were changed as shown in Table 3.

[0182] (Production Example of Protective Layer Coating Liquid 101)

[0183] 70 parts of the hole transporting compound represented by structural formula (3), 10.5 parts of particles S1, 21 parts of melamine-formaldehyde condensate particles having an average particle size of 0.4 μm (product name: EPOSTAR S6, manufactured by Nippon Shokubai Co., Ltd.), 30 parts of 1,1,2,2,3,3,4-heptafluorocyclopentane and 30 parts of 1-propanol were mixed to obtain a protective layer coating liquid 101.

[0184] (Production Example of Protective Layer Coating Liquid 102)

[0185] 70 parts of the hole transporting compound represented by structural formula (3), 1.6 parts of particles S1, 3.5 parts of melamine-formaldehyde condensate particles having an average particle size of 0.4 μm (product name: EPOSTAR S6, manufactured by Nippon Shokubai Co., Ltd.), 30 parts of 1,1,2,2,3,3,4-heptafluorocyclopentane and 30 parts of 1-propanol were mixed to obtain a protective layer coating liquid 102.

[0186] (Production Example of Protective Layer Coating Liquid 103)

[0187] Antimony-doped tin oxide (hereinafter, referred to as ATO) fine particles (product name: T-1, manufactured by Mitsubishi Materials Electronic Chemicals Co., Ltd., average particle diameter: 10 nm to 15 nm) were used as raw material inorganic particles.

[0188] The following materials were prepared in such amounts that their mixing ratios had the values ​​shown below with respect to the ATO fine particles.

[0189] 1H,1H,2H,2H-nonafluorohexyltrimethoxysilane (product name: T2918, manufactured by Tokyo Chemical Industry Co., Ltd.) used as a fluorine-based silane coupling agent 10 mass%

[0190] Octenyltrimethoxysilane (product name: KBM1083, manufactured by Shin-Etsu Chemical Co., Ltd.) used as a polymerizable silane coupling agent 4 mass%

[0191] Isopropyl alcohol (IPA) used as a dispersion solvent (manufactured by Kishida Chemical Co., Ltd., special grade reagent 99.5%) 200 mass%

[0192] These materials were mixed and dispersed using a bead mill to prepare an ATO fine particle dispersion. The dispersion time was set to 90 hours.

[0193] Then, prepare the following materials.

[0194] · 2-Methyl-1-(4-methylthiophenyl)-2-morpholino-1-propanone (product name: Irgacure 907, manufactured by BASF Japan) used as a polymerization initiator 10 parts by mass

[0195] · Multifunctional fluorine-modified acrylic resin used as a photocurable resin (product name: ACU-3, manufactured by KantoDenka Kogyo Co., Ltd.) 100 parts by mass

[0196] Isopropyl alcohol (IPA) used as a dispersion solvent (manufactured by Kishida Chemical Co., Ltd., special grade reagent 99.5%) 150 parts by mass

[0197] Polytetrafluoroethylene (PTFE) fine particles used as fluororesin fine particles (product name: KTL1N, manufactured by Kitamura Limited, average particle size: 2.3 μm, maximum particle size: 4.62 μm)

[0198] 30 parts by mass

[0199] These materials were mixed and added to 100 parts by mass of the above-mentioned ATO fine particle dispersion. Thereafter, the materials were mixed and stirred under light shielding conditions, and the components in the mixed solution were dispersed in the dispersion solvent while irradiating the mixed solution with ultrasonic waves oscillated from an ultrasonic oscillator (oscillation frequency: 40 kHz, ultrasonic output: 50 W) for 5 minutes, thereby preparing a protective layer coating solution 103.

[0200] <Production of Electrophotographic Photosensitive Member>

[0201] Production Example of Electrophotographic Photosensitive Member

[0202] (Production Example of Photosensitive Member 1)

[0203] An aluminum cylinder having a diameter of 30 mm and a length of 357.5 mm was used as a support (cylindrical support).

[0204] Next, 60 parts of tin oxide-coated barium sulfate particles (product name: Passtran PC1, manufactured by Mitsui Mining & Smelting Co., Ltd.), 15 parts of titanium oxide particles (product name: TITANIX JR, manufactured by Tayca Corporation), 43 parts of resol type phenolic resin (product name: PHENOLITE J-325, manufactured by Dainippon Ink and Chemicals, Incorporated, solid content: 70% by mass), 0.015 parts of silicone oil (product name: SH28PA, manufactured by Toray Silicone Co., Ltd.), 3.6 parts of silicone resin particles (product name: Tospearl 120, manufactured by Toshiba Silicone Co., Ltd.), 50 parts of 2-methoxy-1-propanol and 50 parts of methanol were placed in a ball mill and dispersed for 20 hours to prepare a conductive layer coating liquid. The conductive layer coating liquid was applied onto the support by dip coating, and the resulting coating film was heated at 140° C. for 1 hour to be cured, thereby forming a conductive layer having a thickness of 15 μm.

[0205] Next, 10 parts of copolymer nylon (product name: Amilan CM8000, manufactured by Toray Industries, Inc.) and 30 parts of methoxymethylated 6-nylon resin (product name: TORESIN EF-30T, manufactured by Teikoku Kagaku Sangyo KK) were dispersed in a mixed solvent of 400 parts of methanol and 200 parts of n-butanol to prepare a primer coating liquid. The primer coating liquid was applied to the conductive layer by dip coating, and the resulting coating film was dried at 100° C. for 30 minutes to form a primer layer having a thickness of 0.45 μm.

[0206] Next, 20 parts of hydroxygallium phthalocyanine crystals (charge generating material) in the form of crystals having strong peaks at Bragg angles 2θ±0.2° of 7.4° and 28.2° in CuKα characteristic X-ray diffraction, 0.2 parts of a calixarene compound represented by the following structural formula (A),

[0207]

[0208] 10 parts of polyvinyl butyral (product name: S-LEC BX-1, manufactured by Sekisui Chemical Co., Ltd.) and 600 parts of cyclohexanone were put into a sand mill using glass beads each having a diameter of 1 mm. Then, the contents were subjected to a dispersion treatment for 4 hours, and then 700 parts of ethyl acetate were added to prepare a charge generation layer coating liquid. The charge generation layer coating liquid was applied to the undercoat layer by dip coating, and the resulting coating film was dried at 80° C. for 15 minutes to form a charge generation layer having a thickness of 0.17 μm.

[0209] Next, 30 parts of a compound represented by the following structural formula (B) (charge transporting compound (hole transporting compound)), 60 parts of a compound represented by the following structural formula (C) (charge transporting compound (hole transporting compound)), 10 parts of a compound represented by the following structural formula (D) (charge transporting compound (hole transporting compound)), 100 parts of a polycarbonate resin (product name: Iupilon Z400, manufactured by Mitsubishi Engineering-Plastics Corporation, bisphenol Z type polycarbonate) and 0.02 parts of a polycarbonate having two structural units represented by the following formula (E) (viscosity average molecular weight Mv: 20,000) were dissolved by mixing with 271 parts of o-xylene, 256 parts of methyl benzoate and 272 parts of dimethoxymethane (methylal). The solution was applied onto the charge generating layer by dip coating, and the resulting coating was dried at 120° C. for 50 minutes to form a charge transport layer having a thickness of 18 μm.

[0210]

[0211] Next, the protective layer coating liquid 1 was applied to the charge transport layer by dip coating, and the resulting coating was dried at 50°C for 5 minutes. After drying, the coating was irradiated with an electron beam for 1.6 seconds under a nitrogen atmosphere at an accelerating voltage of 60 kV and an absorbed dose of 8,000 Gy. The oxygen concentration during the period from irradiation with an electron beam to heat treatment for 1 minute was 20 ppm. After that, the temperature was raised from 25°C to 110°C in a nitrogen atmosphere within 10 seconds. Next, in the atmosphere, the coating was heat-treated at 100°C in a drying furnace for 10 minutes to form a protective layer having a thickness of 5 μm. The resulting electrophotographic photosensitive member is referred to as "photosensitive member 1".

[0212] Next, the surface layer was cut into pieces having a size of 10 mm square at a position 180 mm from the upper end of the obtained photosensitive member 1. The cross section was subjected to PtPd sputtering from the surface side and then protected with a photocurable resin and a cover glass. An ion beam irradiation apparatus (IM4000, manufactured by Hitachi High-Technologies Corporation) was used to prepare the sample.

[0213] The cross section of the surface layer was observed using a scanning electron microscope (SU8220, manufactured by Hitachi High-Technologies Corporation), and its image was acquired and binarized (Photoshop CS, manufactured by Adobe). (Smα) / (Sα) and (Sm′α) / (Sα) were calculated based on the obtained image. The results are shown in Table 3.

[0214] (Production Example of Photosensitive Members 2 to 24)

[0215] Electrophotographic photosensitive members were produced in the same manner as in the production example of photosensitive member 1, except that the protective layer coating liquid shown in Table 3 was used and the protective layer thickness was adjusted as shown in Table 3. The obtained electrophotographic photosensitive members are referred to as "photosensitive members 2 to 24". The details are shown in Table 3.

[0216] (Production Example of Photosensitive Member 101 and Photosensitive Member 102)

[0217] Electrophotographic photosensitive members 101 and 102 were produced in the same manner as in Production Example of Photosensitive Member 1 except that the protective layer coating liquid shown in Table 3 was used and the protective layer thickness was adjusted as shown in Table 3. The details are shown in Table 3.

[0218] (Production Example of Photosensitive Member 103)

[0219] The same steps as those in the production example of the photosensitive member 1 were performed until the charge transport layer was formed. Thereafter, the protective layer coating liquid 103 was applied by dip coating, and the solvent was dried at 80° C. for 10 minutes. After drying, a metal halide lamp (product name: M08-L41C, Iwasaki Electric Co., Ltd.) was used to irradiate the photosensitive member with UV light at 3,000 mJ / cm 2 The dried coating film on the conductive support was irradiated with a UV dose of 250 W / cm to cure the photocurable resin in the dried coating film, thereby forming a protective layer with a thickness of 3 μm. Thus, an electrophotographic photosensitive member 103 was produced. While the conductive support was rotated at a position where the distance from the metal halide lamp was in the range of 15 cm to 20 cm, the irradiation intensity was controlled at 250 W / cm 2Up to 300W / cm 2 3,000 mJ / cm 2 of UV dose.

[0220] [evaluate]

[0221] (Evaluation of Photosensitive Member 1)

[0222] The photosensitive member 1 was mounted on the cyan station of a modified machine of an electrophotographic apparatus (copier) manufactured by Canon Inc. (product name: imageRUNNER (trademark) ADVANCE C5560) serving as an evaluation apparatus. Under a 10° C. / 5% RH environment, the conditions of the charging device and the image exposure device were set so that the electrophotographic photosensitive member placed on the cyan station of the evaluation apparatus had a dark area potential (Vd) of −700 V and a light area potential (Vl) of −200 V. Thus, the initial potential of the electrophotographic photosensitive member was adjusted in advance.

[0223] Under the above conditions, an evaluation chart of an A4 lateral 5% image was output on 100,000 sheets in an intermittent manner of 5 sheets. After that, the thickness of the protective layer of the photosensitive member used was measured using a multi-channel spectrometer (product name: MPCD9800 / 916C, manufactured by Otsuka Electronics Co., Ltd.) to measure the reduction in thickness (amount of wear due to long-term use). The amount of wear was 0.33 μm. Subsequently, a halftone image with a cyan density of 30% formed by a screen pattern was output, and by comparison with the photosensitive member, the presence or absence of image defects caused by deep cracks of the photosensitive member was determined. The results are shown in Table 3.

[0224] (Evaluation of Photosensitive Members 2 to 24)

[0225] In all cases, evaluation was performed in the same manner as in the evaluation of Photosensitive Member 1, except that the electrophotographic photosensitive members shown in Table 3 were used.

[0226] (Evaluation of Photosensitive Members 101 to 103)

[0227] In all cases, evaluation was performed in the same manner as in the evaluation of the photosensitive member 1, except that the electrophotographic photosensitive members shown in Table 3 were used. The results are shown in Table 3. With respect to the rank, evaluation was performed as described below.

[0228] (Amount of wear)

[0229] A: less than 0.4μm

[0230] B: 0.4 μm or more and less than 0.7 μm

[0231] C: 0.7 μm or more and less than 0.8 μm

[0232] D: 0.8 μm or more and less than 1.0 μm

[0233] E: 1.0μm or more

[0234] (Image defects due to deep cracks)

[0235] A: The cracks on the photosensitive member do not appear as image defects, or are not noticeable but are at a level where there is no problem in image quality.

[0236] B: Cracks on the photosensitive member appear as image defects.

[0237] Table 3

[0238]

[0239] As described through the embodiments and examples, according to one aspect of the present disclosure, an electrophotographic photosensitive member having high wear resistance can be provided.

[0240] While the present invention has been described with reference to exemplary embodiments, it is to be understood that the invention is not limited to the disclosed exemplary embodiments. The scope of the claims is to be accorded the broadest interpretation so as to encompass all such modifications and equivalent structures and functions.

Claims

1. An electrophotographic photosensitive member comprising: Support body; a charge generating layer; and charge transport layer, The charge generating layer and the charge transporting layer are arranged on the support, Characterized in that the surface layer of the electrophotographic photosensitive member comprises: Composite particles, The composite particles comprise: Inorganic particles α having an average primary particle diameter Lα of 5 nm or more and 50 nm or less; and Resin particles β having an average primary particle diameter Lβ of 0.1 μm or more and 5.0 μm or less, and wherein in any cross section of the surface layer, the following formula (1) is satisfied, wherein a region within a distance of Lβ / 2 from the surface of each of the resin particles β is defined as a region M, the sum of the cross-sectional areas of the inorganic particles α present in the cross section is represented by Sα, and the sum of the cross-sectional areas of the inorganic particles α contained in the region M is represented by Smα, and (Smα) / (Sα)≥0.3 Formula (1), wherein the inorganic particles α are selected from silica particles and alumina particles, and wherein the inorganic particles α in the surface layer each have a surface treated with silicone oil or with at least one compound selected from the group consisting of compounds represented by the following structural formulae (1) and (2), In the structural formulas (1) and (2), R 1 ~R 3 Each independently represents an alkoxy group or an alkyl group, provided that R 1 ~R 3 At least two of them each represent an alkoxy group; R 4 represents vinyl, 1-methylvinyl, acryloyloxy or methacryloyloxy; R 5 represents an acryloyloxy group or a methacryloyloxy group; and "n" represents an integer of 1 to 6. 2 . The electrophotographic photosensitive member according to claim 1 , wherein the resin particles β comprise particles of a resin selected from a fluorine resin, a polymethyl methacrylate resin, and a melamine-formaldehyde polycondensation type melamine resin. 3 . The electrophotographic photosensitive member according to claim 1 , wherein an average particle diameter Lβ of the primary particles is 0.1 μm or more and 1.5 μm or less.

4. The electrophotographic photosensitive member according to claim 1, wherein in any cross section of the surface layer, the following formula (2) is satisfied, (Smα) / (Sα)≥0.5 formula (2).

5. The electrophotographic photosensitive member according to claim 1, wherein the following formula (3) is satisfied, wherein a region within a distance of Lβ / 3 from the surface of each of the resin particles β is defined as a region M′, the sum of the cross-sectional areas of the inorganic particles α present in any cross section of the surface layer is represented by Sα, and the sum of the cross-sectional areas of the inorganic particles α contained in the region M′ is represented by Sm′α, (Sm′α) / (Sα)≥0.3 Formula (3).

6. A processing box comprising an electrophotographic photosensitive member; and at least one unit selected from the group consisting of a charging unit, a developing unit, and a cleaning unit, The process cartridge integrally supports the electrophotographic photosensitive member and the at least one unit, and the process cartridge is detachably mountable to a main body of the electrophotographic apparatus, in, The electrophotographic photosensitive member includes a support, and a charge generating layer and a charge transporting layer on the support, Characterized in that the surface layer of the electrophotographic photosensitive member comprises: Composite particles, The composite particles comprise: Inorganic particles α having an average primary particle diameter Lα of 5 nm or more and 50 nm or less; and Resin particles β having an average primary particle diameter Lβ of 0.1 μm or more and 5.0 μm or less, and wherein in any cross section of the surface layer, the following formula (1) is satisfied, wherein a region within a distance of Lβ / 2 from the surface of each of the resin particles β is defined as a region M, the sum of the cross-sectional areas of the inorganic particles α present in the cross section is represented by Sα, and the sum of the cross-sectional areas of the inorganic particles α contained in the region M is represented by Smα, and (Smα) / (Sα)≥0.3 Formula (1), wherein the inorganic particles α are selected from silica particles and alumina particles, and wherein the inorganic particles α in the surface layer each have a surface treated with silicone oil or with at least one compound selected from the group consisting of compounds represented by the following structural formulae (1) and (2), In the structural formulas (1) and (2), R 1 ~R 3 Each independently represents an alkoxy group or an alkyl group, provided that R 1 ~R 3 At least two of them each represent an alkoxy group; R 4 represents vinyl, 1-methylvinyl, acryloyloxy or methacryloyloxy; R 5 represents an acryloyloxy group or a methacryloyloxy group; and "n" represents an integer of 1 to 6.

7. An electronic photographic device comprising: Electrophotographic photosensitive member; and at least one unit selected from the group consisting of a charging unit, an exposure unit, a developing unit, and a transfer unit, wherein the electrophotographic photosensitive member comprises a support, and a charge generating layer and a charge transporting layer on the support, Characterized in that the surface layer of the electrophotographic photosensitive member comprises: Composite particles, The composite particles comprise: Inorganic particles α having an average primary particle diameter Lα of 5 nm or more and 50 nm or less; and Resin particles β having an average primary particle diameter Lβ of 0.1 μm or more and 5.0 μm or less, and wherein in any cross section of the surface layer, the following formula (1) is satisfied, wherein a region within a distance of Lβ / 2 from the surface of each of the resin particles β is defined as a region M, the sum of the cross-sectional areas of the inorganic particles α present in the cross section is represented by Sα, and the sum of the cross-sectional areas of the inorganic particles α contained in the region M is represented by Smα, and (Smα) / (Sα)≥0.3 Formula (1), wherein the inorganic particles α are selected from silica particles and alumina particles, and wherein the inorganic particles α in the surface layer each have a surface treated with silicone oil or with at least one compound selected from the group consisting of compounds represented by the following structural formulae (1) and (2), In the structural formulas (1) and (2), R 1 ~R 3 Each independently represents an alkoxy group or an alkyl group, provided that R 1 ~R 3 At least two of them each represent an alkoxy group; R 4 represents vinyl, 1-methylvinyl, acryloyloxy or methacryloyloxy; R 5 represents an acryloyloxy group or a methacryloyloxy group; and "n" represents an integer of 1 to 6.